88.1k views
1 vote
Write an expression for the sequence of operations described below. Multiply u by t, subtract the result from v, then triple what you have. DOMT SIMPLIFY

User Harryhorn
by
4.9k points

2 Answers

2 votes

Answer:


3(v - ut)

Explanation:

You need to transform from ordinary language to a math language:

Multiply u by t:
u.t

Subtract the result from v:
v - ut (In this case, ut is after the ''-'' signed, you can deduct this when it says ''subtract the result from'')

Triple what you have:
3(v - ut) (meaning just a multiplication of the expression with the number 3).

User Aroldo
by
5.0k points
1 vote

Answer:

The expression is 3(v - ut)

Explanation:

* Lets explain how to solve the problem

- There are some words we can change them to mathematics symbols

# Add ⇒ +

# Subtract ⇒ -

# Multiply ⇒ ×

# Divide ⇒ ÷

- Ex:

# Add x and 6 ⇒ x + 6

# Subtract 7 from y ⇒ y - 7

# Multiply 5 by m ⇒ 5 × m = 5m

# Divide n by 2 ⇒ n ÷ 2 = n/2

* Lets solve the problem

- We want to write an expression for the sequence of operations

described below

- Multiply u by t, subtract the result from v, then triple what you have

* Lets make these operations

- Multiply u by t

∴ u × t = ut

- Subtract the result from v

- Means take ut from v, so v will come first

∵ The result is ut

v - ut

- Triple what you have

∵ Triple means multiply by 3

∵ we have (v - ut)

3(v - ut)

* The expression is 3(v - ut)

User Sergey Podobry
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.